2002
DOI: 10.1007/pl00000319
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins and nitric oxide in gastric damage induced by metamizol in rats

Abstract: In addition to inhibition of PG synthesis, damage induced by metamizol was associated with an inhibition of the NO/cGMP pathway and cNOS activity. In contrast, diclofenac-induced gastric damage was associated with an increase of the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
7
0
2
Order By: Relevance
“…However, 3 of 12 volunteers treated with the high dose of dipyrone developed relevant lesions, suggesting a dose-dependent mucosa-damaging effect in some individuals probably due to the somewhat higher and sustained inhibition of COX-1. Moreover, other mechanisms such as diminished glutathione metabolism (58) or inhibition of the nitric oxide/cyclic guanosine monophosphate pathway and nitric oxide synthase activity (59), which have been suggested to contribute to high-dose dipyrone-elicited weak mucosal lesions in rats, appear feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 of 12 volunteers treated with the high dose of dipyrone developed relevant lesions, suggesting a dose-dependent mucosa-damaging effect in some individuals probably due to the somewhat higher and sustained inhibition of COX-1. Moreover, other mechanisms such as diminished glutathione metabolism (58) or inhibition of the nitric oxide/cyclic guanosine monophosphate pathway and nitric oxide synthase activity (59), which have been suggested to contribute to high-dose dipyrone-elicited weak mucosal lesions in rats, appear feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of COX have been identified: COX-1, a constitutive enzyme that appears to be responsible for the production of PGs that are physiologically important for homeostatic functions, and COX-2, an inducible isoform, dramatically upregulated during certain processes synthesizing PGs, mediating inflammation, fever and pain [34,35]. However, many studies in recent years have suggested that COX-2 can contribute to gastric mucosal control at least in some circumstances such as adaptive response of gastric mucosa to a topical irritant [36], colonization by Helicobacter pylori [37], healing of chronic gastrointestinal ulcer [38] or defense mechanisms in the damage induced by NSAIDs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their role in the pathophysiological mechanisms underlying some relevant inflammatory disorders, the possible interaction between NO and PG biosynthetic pathways has been studied to verify a possible combined approach in the treatment of many disease states (Fig. 4) (Abramson et al, 2001;Mebazaa et al, 2001;Beierwaltes, 2002;Davel et al, 2002;Gallo et al, 2002;Naoki et al, 2002;Sanchez et al, 2002;Shinmura et al, 2002;Takeuchi et al, 2002;VayssettesCourchay et al, 2002;Kawabe et al, 2003;Slomiany and Slomiany, 2003).…”
Section: A Nitric Oxide/cyclooxygenase Reciprocal Interactionsmentioning
confidence: 99%